PENGARUH FIRM VALUE DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING - Stefanie Stefanie; Widyasari Widyasari (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to gain empirical evidence about the effect of profitability, leverage, and institutional ownership on firm value moderated by corporate social responsibility (CSR) in property and real estate companies listed in Indonesia Stock Exchange for 2017-2019. This research used 120 samples of property and real estate companies selected through purposive sampling technique. The data used are secondary data in the form of company annual reports. The data are processed using Eviews version 11. The results of this research indicate that profitability has no effect on firm value, leverage has a positive effect on firm value, institutional ownership has no effect on firm value, CSR is unable to moderate the effect of profitability on firm value, CSR weakens the effect of leverage on firm value, and CSR is unable to moderate the effect of institutional ownership on firm value.